Effect of trace and residual elements on the hot brittleness, hot shortness and properties of 0.15-0.3 % C Al-killed steels with a solidification microstructure - Torkar, Matjaž (Materiali in tehnologije, 2010)
The formation of cracks in steels with a solidification microstructure is connected with either the precipitation and segregation of residual elements during solidification and/or with the accumulation of some residual elements at the scale-metal interface during the soaking of the blocks. Hot-brittlenessis connected with the change in the solubility of the trace elements in the solid solution of austenite, with segregations of the surface-active elements to the grain boundaries, with the precipitation of small particles at the grain boundaries during solidification and cooling to the hot working temperature, and with the effect of some elements on the solidification microstructure. In this article an overview of the hot brittleness of steels cast in the peritectic range is presented.
Keywords: jekla; strjevanje; mikrostruktura; krhkost; pokljivost; izcejanje; izločanje; oligoelementi; meje med zrni